VD_FINDINFO HC / 2012 / 322 vom 16. April 2012 - VD Tribunal cantonal (2012)
RETRAITVOIE DE DROIT, BAIL À LOYER, PROPOSITIONMV, EFFET, CONCLUSIONS, DEMANDEACTION EN JUSTICE | 210 CPC (CH), 211 al. 2 CPC (CH), 236 CPC (CH), 241 CPC (CH), 308 al. 1 let. a CPC (CH)